2019
DOI: 10.1111/hel.12579
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of histologic atrophy and intestinal metaplasia in the corpus has decreased over 15 years in females in the Korean population

Abstract: Background The aim of this study was to investigate the trends of atrophy and intestinal metaplasia (IM) in 2002 subjects without significant gastroduodenal diseases. Materials and Methods A total of 2002 subjects were prospectively enrolled and divided into three periods (2003‐2007, 2008‐2012, and 2013‐2018). Trends of H pylori and atrophy/IM scored by Updated Sydney System were analyzed according to sex, and multivariate logistic analysis was performed for the risk factors for atrophy/IM. Results H pylori‐ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 57 publications
(101 reference statements)
1
6
0
Order By: Relevance
“…Bounder et al reported in his study 11.7% of AG and 7.4% of IM. We found that 80% of our atrophic gastritis form were related to Helicobacter Pylori infection, such findings are supported by a substantial number of studies [34,38,39]. Asaka et al reported the same prevalence (the prevalence of atrophic gastritis in H. pylori infection was 82.9%) [40].…”
Section: Discussionsupporting
confidence: 81%
“…Bounder et al reported in his study 11.7% of AG and 7.4% of IM. We found that 80% of our atrophic gastritis form were related to Helicobacter Pylori infection, such findings are supported by a substantial number of studies [34,38,39]. Asaka et al reported the same prevalence (the prevalence of atrophic gastritis in H. pylori infection was 82.9%) [40].…”
Section: Discussionsupporting
confidence: 81%
“…16 The development of gastric cancer is strongly associated with a high prevalence of histological atrophy and GIM (37.7/29.6% in the antrum and 20.6/16.8% in the corpus, respectively). 17 The operative link on gastritis assessment (OLGA) and OLGIM enable the systematic evaluation of individual gastric cancer risk. 18 The proportion of high-risk OLGA and OLGIM stages has been reported to be 23.0/11.5%, 29.1/14.2%, and 41.1/30.1% at the ages of the 40s, 50s, and 60s, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In South Korea, the age‐standardized incidence of gastric cancer in 2020 was 25.7 per 100 000 16 . The development of gastric cancer is strongly associated with a high prevalence of histological atrophy and GIM (37.7/29.6% in the antrum and 20.6/16.8% in the corpus, respectively) 17 . The operative link on gastritis assessment (OLGA) and OLGIM enable the systematic evaluation of individual gastric cancer risk 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, gastric atrophy may be regulated by molecularly distinct mechanisms to that of intestinal metaplasia (i.e., aberrant expression of CDX proteins). In other words, improvement of gastric atrophy after H. pylori eradication may be independent of changes in intestinal metaplasia [15,16,17,18,19,20], which seems to be a more sustained, stable reprogramming event of the gastric glands. In our study, the expression of CDX1 was more closely associated with changes in the intestinal metaplasia score than that of CDX2.…”
Section: Discussionmentioning
confidence: 99%